Specprof: a Tool for Biological Indexing - Obioh, Gloria I. B.; Isichei, Augustine O. (Nigerian Conservation Foundation (NCF), 2014)
The development of a comprehensive information base is one of the most compelling needs in conservation as it can contribute to coordinated conservation efforts. In biodiversity conservation, indexing of organisms is of great importance because it sets the stage for investigating their relationships to other organisms. In view of recent trends in information and communication technology, electronic archiving of available data on the species is needed as a primary step to biodiversity conservation. A species profile (SPECPROF) database, an electronic data archiving, vouchering and retrieval system has been developed to support plant diversity indexing in a wide range of ecosystems. SPECPROF is an application database developed in the Microsoft Windows environment. The fields in SPECPROF are structured using the Microsoft Access 2000 database programme with Visual Basic providing the Graphical User Interface front end. It allows users to input, query and display information available on species. It is a fast and easy conservation tool for use in biological indexing.